STEM-PjBL Learning: The Impacts on Students’ Critical Thinking, Creative Thinking, Communication, and Collaboration Skills - Kurniahtunnisa Kurniahtunnisa; Yustinus Ulung Anggraito; Saiful Ridlo; Fransiska Harahap (Postgraduate, University of Mataram, 2023)
The purpose of this study was to analyze the effectiveness of STEM-PjBL learning on students' critical thinking, creative thinking, communication, and collaboration (4C) skills. This research is quantitative with a one-group pretest-posttest design. The research samples were 106 class XI State Senior High School 16 Semarang students. Quantitative data on critical thinking skills were analyzed using the N-gain test, while other data were analyzed descriptively. The results showed increased students' critical thinking skills based on the N-gain test. The paired sample t-test results in the SPSS 28 program obtained a significance value/Sig. (2-tailed) of 0.001, there were differences in critical thinking skills before and after STEM-PjBL learning. STEM-PjBL learning effectively trained students' creative, collaborative, and communicative thinking skills with high categories. This learning effectively trained students' critical thinking, creative thinking, communication, and collaboration skills